Audit Tenure, Audit Fee and Audit Quality: The Mediating Role of Firm Size - Juju Nuryanti; Rd. Amar Muslih; Lina Yulianti (Journal of Applied Accounting, 2026)
Recurrent irregularities in auditing practices across the globe, Indonesia included, have intensified the call for rigorous scrutiny of the factors that shape audit quality and the integrity of financial reporting. Concurrently, the swift growth of the Islamic capital market has elevated the need for reliable and ethically grounded disclosure. Drawing on a sample of food and beverage manufacturers listed on the Indonesian Sharia Stock Index (ISSI) over the 2021–2024 window, this study examines whether audit tenure and audit fee predict audit quality, and whether firm size acts as an intermediary in those relationships. The novelty of this study lies in its exclusive focus on ISSI-listed food and beverage firms a context that has been systematically underexplored in prior audit quality research  and its simultaneous treatment of firm size as a mediating variable rather than as a control or moderating variable, offering a distinct analytical contribution to the audit quality literature in the Islamic capital market setting. A positivist, quantitative design was applied, employing multiple linear regression, binary logistic regression, and path analysis. Secondary data sourced from the annual financial statements of 24 companies generated 96 firm-year observations through purposive sampling. The Big Four/non-Big Four dichotomy was used as the audit quality proxy, following DeAngelo (1981) and Lumban Gaol and Sitohang (2020), with the acknowledgment that this proxy captures reputational rather than technical quality differences. Results reveal that: (1) audit tenure exerts no statistically significant influence on audit quality; (2) audit fee positively and significantly drives audit quality; (3) firm size has no significant bearing on audit quality; (4) audit tenure does not significantly determine firm size; (5) audit fee positively and significantly predicts firm size; (6) firm size fails to transmit the effect of audit tenure onto audit quality; and (7) firm size likewise fails to transmit the effect of audit fee onto audit quality. These findings establish audit fee as the dominant direct driver of audit quality in the ISSI food and beverage sector, operating independently of firm scale. Keywords: audit tenure, audit fee, firm size, audit quality, Big Four auditor, Islamic capital market, Indonesian Sharia Stock